Basketball at the most magical place on earth: A case study of the NBA's season conclusion at Walt Disney World amid the COVID-19 pandemic - Havard, C. T. (SAGE Business Cases, 2020)
The case study follows the National Basketball Association`s (NBA) attempt to complete the 2019-2020 season at the ESPN Wide World of Sports at Walt Disney World amid the COVID-19 Pandemic. When the season was officially placed on hiatus in March 2020, players, fans, and administrators were unsure if the season would be finished at a later date and what a conclusion would look like. When the NBA announced their season would conclude at Walt Disney World outside of Orlando, Florida, many parties and stakeholders rejoiced while others questioned whether the league should finish the season and the place sport served in the public dealing with the pandemic. After providing details about the NBA`s decision to complete their season at Walt Disney World, the case study allows students to discuss and make decisions given foreseeable and unforeseeable circumstances and events.